Assistance to Business Actors Through the Cultivation of Grapefruit Seeds to Improve the Village Economy - Ubaidillah, M. Abi Mahrus; Erwanto, Dian; Baidowi, Achmad; Ngulya, Moh. Tamim Ngizamul; Muhammad Rizky Gymnastiar,; Muhamad Maftuh, (TAAWUN, 2025)
This community service activity aims to increase the capacity of village business actors in the agribusiness sector through the transfer of knowledge and skills in the cultivation of sustainable and high economic value grapefruit seeds. The approach used is the Asset-Based Community Development (ABCD) method, which focuses on local potential and assets. These steps include: local potential, determination of goals and expectations, program design, determination of direction and indicators of success, and implementation and sustainability. This activity involved the village community and the owner of PT. Rumawan Pusaka Negeri as a partner. The results of the activity showed an increase in the knowledge and skills of residents in the seeding and grafting techniques of grapefruit seedlings, the formation of a new farmer group "Tani Bibit Lawu", and the emergence of residents' initiatives to develop a nursery business independently. The usefulness of this program is not only reflected in the economic aspect in the form of potential income increases, but also in the social aspect, namely the formation of a cooperation network, the spirit of cooperation, and the strengthening of the village's identity as a center for horticultural seeds. This activity proves that participatory local asset-based interventions can encourage sustainable village social and economic transformation.